Effect of Adsorbed Water and Temperature on the Universal Power Law Behavior of Lepidocrocite-Type Alkali Titanate Ceramics - Saichon Sriphan; Phieraya Pulphol; Thitirat Charoonsuk; Tosapol Maluangnont; Naratip Vittayakorn (The Journal of Physical Chemistry C, 2021)
The ubiquitous (re)adsorption of atmospheric water by functional ceramics leads to some applications such as humidity sensing; at the same time, this phenomenon complicates the understanding of the nature of original conducting species. We presented herein the effects of adsorbed water on the electrical properties and charge transport of K0.8Zn0.4Ti1.6O4, Cs0.7Zn0.35Ti1.65O4, and Cs0.6K0.1Zn0.35Ti1.65O4 lepidocrocite-type alkali titanate ceramics. A small amount of atmospheric water (0.02–0.33 mol/mol) is merely adsorbed on the external surface but not intercalated into the interlayer space. In temperature scan experiments, water sorption leads to the dielectric permittivity/loss hysteresis loops, where the values upon cooling are unusually larger than those upon heating. In frequency scan experiments, multiple frequency- and temperature-dependent anomalies are detected. The AC conductivity was fitted to the Jonscher universal power law response (σ′AC = σDC + Aωs) from 101 to 106 Hz and 400–25 °C. We observed an uncommon U-shaped A(T) but an inverted U-shaped s(T), regardless of the interlayer ion, charge per formula unit, or pellet density. These plots allow a qualitative description of (i) the apparent activation energy, (ii) the effective dimension of the conduction pathway, and (iii) the charge carrier concentration, all as a function of the temperature under the influence of atmospheric water. Our physical interpretation is potentially applicable to other systems, providing insights into the (unintentional) water-induced conductions and complementing rigorous but time-consuming investigations by controlled humidity experiments.
Keywords: Ferroelectric and Piezoelectric Materials; Dielectric properties of ceramics; Microwave Dielectric Ceramics Synthesis